HASIL BELAJAR MATEMATIKA DAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION SISWA KELAS III SD N KARANGTENGAH BARU - Mela Selfia; Ag. Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe the increase in activity and mathematics study result of third grade students of Karangtengah Baru State Elementary School with Realistic Mathematic Education (RME). TheÂ type of this research is Classroom Action Research (CAR). The study was conducted in two cycles. Data collection techniques used observation, tests, and documentation. The research instrument used validity, difficulty, difference, and reliability testing. The technique of analyzing student activeness data by calculating the average percentage of student activity, while for the learning outcomes test is done by calculating the class average value and calculating the percentage of classical completeness. The results of the study showed that after applying the RME, student activity and learning outcomes increased. This can be shown in the increase in the final results of each cycle, in the pre cycle the average percentage of class activity is only 60%, in the first cycle the average percentage of class activity has increased 69.30%, and in the second cycle increase to 80.16%. The percentage increase in student learning outcomes from pre-action was 50.00%, increased in the first cycle was 62.50%, and in the second cycle was 87.50%. The results of this research are input so that third grade students of Karangtengah Baru State Elementary School can apply RMEÂ as one of the more alternative learning alternatives.